Giant Cell Tumor of Bone in a Child with Goltz Syndrome. (July 2013) - Shao, Lei; Mardis, Neil; Nopper, Amy; Jarka, Dale; Singh, Vivekanand
Giant cell tumor of bone is a neoplasm that is rarely seen in children. Goltz syndrome is a disorder that affects multiple ectodermal and mesodermal tissues and has occasionally been associated with giant cell tumors of bone. Our case of giant cell tumor in a 5-year-old girl with Goltz syndrome suggests that this syndrome provides a unique situation wherein the practitioner should consider giant cell tumor of bone, even in a pediatric setting.